Analysis of coastline change in relation to meteorological conditions and human activities in Ca mau cape, Viet Nam. (1st April 2019) - Thoai, Duong Thanh; Dang, Anh Nguyet; Kim Oanh, Nguyen Thi
Abstract: Ca Mau Cape is a part of Ngoc Hien district and is the southernmost tip of inland Vietnam. The district is highly vulnerable to coastal processes induced by natural and human factors that play important role in shaping and controlling the coastline. This study investigated the coastline change over 20 years, 1990–2010, in relation to meteorological conditions and human interventions using the land-use map (Landsat TM) and questionnaire survey. During this period, Ngoc Hien lost 2206 ha of coastal zone due to erosion. Most of the erosion occurred in the communes located in the east coast side. Remarkable changes in land-use/land-cover patterns were observed with a substantial reduction in the forest and increase in the aquaculture farming land. The results of the technical data analysis and questionnaire survey showed that both meteorological conditions and human interventions were interacted to cause the changes. Although the impacts of individual factors could not be readily quantified, the most important factors causing the coastline changes were forest area loss, river dredging, aquaculture and infrastructure development. The scientific information obtained in this study can be used to develop sustainable coastal management strategies for the study area. Highlights: Coastline changes during 1990–2010 were analyzed using Landsat image. Household and expert surveys were conducted. Aquaculture and infrastructure development, river dredging were key human interventions. Climate conditions and human interventions complexly interacted to cause the change.